The Relationship Between Environmental Factors And Acute Respiratory Infections In Rural Areas: A Literature Review - Safira Mohd Akhyar, Athiyah; Solikhah, Solikhah; Wahyuni Sukesi, Tri (Universitas Ahmad Dahlan, 2026)
Background: The incidence of acute respiratory infections (ARI) is a significant global public health issue. One of the risk factors affecting ARI is the environment. The environment and ARI have a cross relationship. This study was conducted to clearly determine the relationship between the environment and the incidence of ARI in rural areas. Method: The article review was conducted by searching for articles through electronic databases (Google Scholar, PubMed, and Semantic Scholar) using the keywords environment, respiratory tract infection, and environmental factors for acute respiratory infection in rural areas. The inclusion criteria used were original articles in national and international accredited journals, the year of publication of the article between 2019 - 2024, full text, free access, and cross sectional research design. Exclusion criteria in this study were literature review or systematic review meta-analysis, related to covid-19, and urban areas. Five articles were selected for analysis. Articles were analyzed by following the Prisma Guidelines. Results: Poor environmental conditions have been identified as a significant risk factor that contributes to the increased prevalence of acute respiratory infections (ARI), particularly in the context of exposure to air pollutants. Furthermore, inadequate environmental conditions have been demonstrated to exacerbate the severity of acute respiratory infections (ARI), as irritated respiratory tracts become more susceptible to invasion by environmental pathogens. These findings underscore the pivotal role of environmental quality, particularly in rural areas, as a crucial predictor of ARI risk and impact.